Depressive Symptoms of the Main Character in Julie Anne Peters’ By the Time You Read This, I Will Be Dead - Rufi Lailatul Septia Ningrum; Robby Satria (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This research aims to determine the psychological problems, namely depression, of the main character in the "By the Time You Read This, I Will Be Dead" novel by Julie Anne Peters. This research uses the theory of Beck & Alford (2009) to analyze symptoms of depression through the attitudes and statements of the main character. The method used is descriptive qualitative research. The results of the research showed a total of 21 data points that showed symptoms of depression in Daelyn Rice. These data are divided into various forms of symptoms, namely 5 data points each from emotional motivations, cognitive manifestations, and motivational manifestations, then 3 data points from vegetative & physical manifestations, 2 data points from delusions, and finally, there is 1 data point on hallucinations. The researcher concluded that of the six forms of symptoms, emotional motivations, cognitive manifestations, and motivational manifestations have the most data compared to other forms of symptoms. This research is significant because it contributes to a deeper understanding of depression and highlights the importance of recognizing early psychological symptoms through literature.